Tissue perfusion rate estimation with compression-based photoacoustic-ultrasound imaging - Choi, Min; James Shapiro, A. M; Zemp, Roger (Journal of biomedical optics, 2018)
Tissue perfusion is essential for transporting blood oxygen and nutrients. Measurement of tissue perfusion rate would have a significant impact in clinical and preclinical arenas. However, there are few techniques to image this important parameter and they typically require contrast agents. A label-free methodology based on tissue compression and imaging with a high-frequency photoacoustic-ultrasound system is introduced for estimating and visualizing tissue perfusion rates. Experiments demonstrate statistically significant differences in depth-resolved perfusion rates in a human subject with various temperature exposure conditions.